Psikologi Pendidikan Islam dalam Al-Qur'an: Psychology of Islamic Education In the Qur'an - Rohimah, Siti; Kholil; Hidayat, Muhtar; Ikhsanuddin, Muhammad; Dian Setiawan Nasir, Rizka (CV. Kalimasada Group, 2024)
The aim of this study was to investigate the ideas of educational psychology contained in the Qur'an and how they affect the psychological health of students. This study examines the verses of the Qur'an related to educational psychology, character formation, motivation, and emotional regulation using qualitative methodology. In order to understand how the lessons of the Qur'an are practically applied in the classroom, the opinions of Islamic educational psychologists are also examined. The findings suggest that the Qur'an offers a thorough guide to help students ' psychological growth in Islamic education. The Qur'anic concepts of fitrah, moral development, motivation, and emotional regulation can be a solid foundation for the development of character and mental health of students. The study offers suggestions to improve the level of Islamic education while strengthening the knowledge and application of Islamic education psychology based on the Qur'an. It is expected that this study can be a guide to Islamic teaching strategies in the future that emphasize more on the moral and mental health of students.